The Antimicrobial Effect Against Multi-drug Resistant Bacteria of the SK4 Peptide: A Novel Hybrid Peptide of Cecropin-A and BMAP-27 - Masadeh, Majed M.; Laila, Salam A.; Haddad, Razan; Alzoubi, Karem; Alhaijaa, Ahmad Abu; Alrabadi, Nasr (Current Pharmaceutical Biotechnology, 2023)
Background: Antibiotic-resistant is considered one of the critical health challenges in the management of infectious diseases. Resistant bacterial strains to different antibacterial agents have been spread worldwide. Anti-microbial peptides (AMPs), also called host defense peptides, have a broad spectrum of activity and targeting even to multi-drug resistant (MDR) bacteria, therefore, they have been extensively studied and developed as novel therapeutic antibacterial agents. Objectives: The study aims to design a novel SK4 hybrid peptide with improved characteristics compared with the BMAP-27 and Cecropin-A natural parents’ peptides. Methods: The bioinformatic analysis of the SK4 peptide compared with the parents BMAP-27 and Cecropin-A peptides was conducted and fully characterized using specialized software. The antimicrobial and antibiofilm activity of SK4 was tested, followed by a synergistic study with five conventional antibiotics (Levofloxacin, Rifampicin, Chloramphenicol, Doxycycline, and Ampicillin). Finally, the cytotoxicity against horse erythrocytes and mammalian cells was assessed. Results: The SK4 peptide demonstrated broad-spectrum antimicrobial activity against both grampositive and gram-negative bacteria. The peptide also did not show any hemolytic activity even when used at concentrations ten folds higher than its MICs value. The SK4 peptide also showed a synergistic mode of action when combined with antibiotics, which resulted in a significant decrease in MIC values for both the peptide and the antibiotics. Conclusion: The SK4 peptide showed better activity, selectivity, and safety profile than the parent peptides, making it a novel potential treatment for MDR bacterial infections.
Keywords: synergy